Trabalho docente e saúde mental de professores brasileiros na pandemia covid-19 - Rodrigues, Haline Maria Parente (2023)
In recent years, there has been significant growth in mental disorders among teachers. Additionally, due to the Covid-19 pandemic, the transition from in-person to remote teaching has accentuated the precariousness of teaching work and, in many cases, has led to increased workload, flexibility processes, and work intensification. The objective of this research is to investigate the predictors of Common Mental Disorders (CMDs) among basic education teachers during the Covid-19 pandemic, considering the work context, variables related to experiences during this period, and sociodemographic characteristics. A total of 14,374 teachers participated in this study. The majority of respondents were from the Northeast region (62.5%), followed by the Southeast (23.6%), Midwest (6.5%), North (5.6%), and South (1.8%) regions. Data collection utilized the Self-Reporting Questionnaire (SRQ-20) for screening Common Mental Disorders, the Remote Teaching Work Context Assessment Scale (EACTDR), along with sociodemographic questions and questions related to the pandemic context. The results showed that approximately a quarter of the sample exhibited indications of CMDs, and regarding the predictors, the variables with the largest effect sizes were, in this order, work organization, socio-professional relationships, age, and gender.